Experimental study on whole process of river blockage and dam break under different hydrodynamic conditions - Niu, Zhipan; Meng, Chuke; Xu, Weilin; Di, Baofeng; Long, Yi; Yang, Hang (Frontiers in Earth Science, 2023)
River blockage and dam break usually occur in mountainous areas with many valleys, and are frequent and extremely harmful natural disasters. With the construction of infrastructures in mountainous areas, the demand for disaster prevention and control has been further increased. Based on an innovative small-scale model for simulating whole process of river blockage and dam break, the present study carried out eight groups tests under different inflow rates. In the analysis, whole process of river blockage and dam break was divided into four stages: ESBK, LSBK, ESBK and LSBK. By analyzing the relationship between Qin and Qmax, it is found that Qmax generally increases with the increase in Qin, but when the change in Qin was small, the result may be opposite. In addition, it is found that the coefficient a increases as d50 increases. Finally, the influence of inflow rate and dam height on Qmax was analyzed using the multiple linear regression method. The increase in Qmax per increase unit Hd was higher, when compared to the increase in Qmax per increase unit. The present study proposes a new method for model experiments, providing new ideas for subsequent model experiments. Furthermore, these conclusions can provide reference for disaster prevention and mitigation in mountainous areas.